A STUDY TO ASSESS THE USAGE OF ARTIFICIAL INTELLIGENCE TOOLS FOR MANUSCRIPT WRITING AMONG MEDICAL PROFESSIONALS – A CROSS-SECTIONAL STUDY - Sagar Chidanand Duganavar; Ajay Sajjanar; Atyanth B Hallikar; Jagadishchandra S Ratnakar; Manjunath Kamble (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Artificial intelligence (AI) refers to computer systems capable of performing complex tasks that were previously only possible for humans. AI's importance is growing in the healthcare sector. In manuscripts AI can be utilized for paraphrasing, generating information, plagiarism checks, Summarizing Long Medical Studies and Translation.Methods: After obtaining clearance from the Institutional Ethical Committee, a cross-sectional study was conducted. A Google Form link was sent to medical professionals. Google Forms consist of various information, which includes demographic details, job titles, and specifics regarding the usage of AI tools. Data was analysed using SPSS.Results: Among 82 responses 54%were females and 46% were males. 40% of participants used AI. For paraphrasing Chat GPT (58%) was used followed by Quillbot (55%). For literature search, Semantic-Scholar (30%) and Connected Papers (30%) were used. For generating information ChatGPT (55%) was used more followed by Co-pilot. For reference management, Zotero (39%) was used more followed by Mendeley (33%). For plagiarism check quillbot (39%) and Grammarly (33%) were popular. To summarize article (63%) didn’t use AI, still, ChatGPT, Claude AI, and copilot were used. For finding the grammatical and typing errors Grammarly (49%) and Chat GPT (9%) were used.Conclusions: AI tools could significantly enhance the quality of academic manuscripts, reducing the time researchers spend on these tasks.